OČUVANJE ZDRAVE ŽIVOTNE SREDINE KROZ ODRŽIVU IZGRADNJU - Civić, Aila; Marič, Miha (International Journal of Economic Practice and Policy, 2025)
Circular economy focuses on the sustainable use of natural resources. A linear model is largely present in the construction industry, which is reflected in the amount of materials used and discarded. Accumulation of construction waste in landfills, in the sea or in nature affects the negative aesthetic appearance. Due to the rigid composition of building materials, it is necessary to study new methods of processing, recycling and reuse, which will have a positive impact on the future of the next generations. The content is divided into a theoretical and an empirical part. In the theoretical part, we defined the circular and linear economy, the construction sector, building materials and waste generated in the construction process. The empirical part shows the answers to the interview we conducted with an expert and research on good practices in Slovenia and abroad. Many sustainability certificates can help us. With various modern materials such as recycled concrete, wood or hemp, we can effectively contribute to a better quality of the living environment. We have found many good practices in Slovenia and abroad, but when taking steps for a better tomorrow, it is important to introduce a circular model to all companies. Implementing a circular economy brings many advantages, including a healthy environment and new and better jobs. The implementation of the circular model in practice brings many obstacles, which are mainly defined by government support, legislation and financial resources.